Immunolocalization of cementum specific proteins CEMP1 and CAP in tumor cells. - Patricia González-Alva; Eduardo Gómez-Plata; Higinio Arzate (Journal of Oral Research, 2013)
Introduction: CEMP1 and CAP are recognized as cementum proteins, they appear to be limited to cementoblasts and their progenitors, and participate in the mineralization process of periodontal ligament tissues, including the proliferation and migration of periodontal ligament fibroblasts. However, their contribution in neoplastic processes had not been explored. In the present study, we investigated their protein expression and localization in cancer tissues and cells. Materials and Methods: CEMP1 and CAP expressions were analyzed immunohistochemically in 13 cancer cases with bone metastasis. In addition, Wester Blot essays were use to detect expression of the proteins in the prostate (PC-3) and mama (MCF-7) cancer cell lines. Results: CAP expression was detected in all tissues examined. Strong cytoplasmatic and rarely nuclear staining was found in small tumor nests, glandular structures and, in the stromal fibroblasts at the immediate vicinity of the tumor nests. CEMP1 was found in the cytoplasm of tumor cells in 5 cases, but its expression was negative in the stromal tissues. Also, cancer lines PC-3 and MCF-7 showed CEMP1 expression; however, CAP expression was observed only in MCF-7 cells. Conclusions: The results suggest that CEMP1 and CAP are present in tissues other that cementum and possibly contribute to pathological conditions such as metastatic cancer.